إشكالية تلقي الخطاب الصوفي - خصوصية الكتـــابـــة الإبداعية -problematic Mystic Communication Is Received Creative Writers Of August's Privacy - رندة, جنينة (Université de M'sila, 2020)
الملخص : تسعى هذه الدراسة إلى محاولة توضيح قضية مهمة تخص الخطاب الصوفي، وتتمثل في خصوصية التجربة الإبداعية الصوفية، من خلال بيان شعرية الخطاب الصوفي وجمالية اللغة الصوفية، وكيف ساهم ذلك في صعوبة تلقي الكتابة الصوفية، وعمل على خلق إشكالية أمام القارئ، في تلقي وتأويل الخطاب الإبداعي الصوفي، فأدى إلى خلق أفق توقع خاص به يحتاج إلى قارئ خاص وخبير يستطيع الغوص في أعماق النص الصوفي وكشف خباياه. Abstract: This study intenol to clarises an important deal concerning the Mystic discourse, wiche is handl the privacy of the creative mystical experience through providing the persection and the beauty upon the language and hour it contributed thought receivieng difficulty of the Sufism writing besides creat some essue in the front of the reader, and interpret receiving the Mystic perfection , wich is caused a one his own horizon expectation needs an expert special reader how can dive into the depths of the depeths of the mystic text and discourse its secrets or his deal.
Keywords: الخطاب الصوفي، خصوصية اللغة، شعرية الكتابة، إشكالية التلقي. ; Key words: Mystic discourse, language privacy ,problematic reception.